Aspergillus-related immune reconstitution inflammatory syndrome in pediatric cancer patients, clinical characteristics, imaging findings, and survival - Ali Amanati; Mehdi Ghaderian Jahromi; Hadis Jafarian; Seyed Reza Abdipour Mehrian; Sarvin Sajedianfard; Shahdad Farokhmanesh; Arman Maddahi; Farima Safari; Seyed Ali Nabavizadeh; Mohammad Matin Karbalaee Alinazari (BMC Infectious Diseases)
Abstract Aspergillus-related immune reconstitution inflammatory syndrome (IRIS) is a challenge to diagnose in immunocompromised pediatric cancer patients with Invasive Pulmonary Aspergillosis (IPA). If not recognized, it can mimic disease progression and lead to overtreatment. Studies on Aspergillus-related IRIS in the pediatric population are scarce. We prospectively identified four pediatric cancer patients diagnosed with IPA who developed paradoxical worsening of pulmonary symptoms following neutrophil recovery. The clinical course, imaging findings, and response to corticosteroids were also reviewed. All patients had refractory respiratory symptoms, including cough, breathing difficulties (dyspnea), and chest pain, despite antifungal therapy. Serial imaging revealed new or enlarging pulmonary infiltrates. Symptoms improved dramatically with corticosteroids without antifungal escalation, confirming Aspergillus-related IRIS diagnosis. Aspergillus-related IRIS can occur in immunocompromised children with cancer and IPA, mimicking disease progression. Recognition is important for avoiding overtreatment. This is the first report highlighting the features of Aspergillus-related IRIS in pediatric cancer patients.